Advances in Latest Application Status, Challenges, and Future Development Direction of Electrospinning Technology in the Biomedical. (19th September 2022) - Wang, Yimin; Lu, Siming; Zheng, Jiayong; Liang, Liguo
Abstract : In recent years, nanotechnology has attracted much attention in the field of biomedicine and sensing technology. As one of the simplest and most effective methods to prepare nanofiber materials, electrospinning technology has a lot of application research in biomedical fields such as sensor detection, drug delivery, and tissue engineering because of its high porosity, large surface area to volume ratio, and uniform size. In this review, we summarized the latest application progress of electrospinning materials in biomedicine, sensing, and textile industry and discussed the challenges and future development direction of electrospinning technology.